2020
DOI: 10.1371/journal.pone.0230359
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer prevention in Indonesia: An updated clinical impact, cost-effectiveness and budget impact analysis

Abstract: Introduction The clinical and economic impact of cervical cancer consistently become a serious burden for all countries, including Indonesia. The implementation of HPV vaccination policy for a big country such as Indonesia requires a strong commitment from several decision-makers. The aim of this study was to provide a comprehensive description on cost-effectiveness and the budget-impact of HPV vaccination policy in Indonesia. Method A cohort Markov model was used to evaluate the cost and the clinical impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…A study showed that HPV vaccination is not cost-effective when the price is above 50 USD per dose, especially for people living in rural areas [ 99 ]. In addition, Indonesia’s self-financing of HPV vaccination policy demands a massive allocation since the country has to supply about five million (two doses x 2.5 million 10-year girls) doses annually [ 100 ]. Furthermore, the vaccination cost must consider the vaccine price, shipping, insurance, and handling fees (i.e., customs clearance, warehouse storage, transportation, and labeling), creating more costly [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that HPV vaccination is not cost-effective when the price is above 50 USD per dose, especially for people living in rural areas [ 99 ]. In addition, Indonesia’s self-financing of HPV vaccination policy demands a massive allocation since the country has to supply about five million (two doses x 2.5 million 10-year girls) doses annually [ 100 ]. Furthermore, the vaccination cost must consider the vaccine price, shipping, insurance, and handling fees (i.e., customs clearance, warehouse storage, transportation, and labeling), creating more costly [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assim, esse jogo pode contribuir para o aumento da taxa de adesão à vacinação, considerada baixa no estudo mencionado. A vacinação mostrou-se uma estratégia econômica e acessível, (32) portanto, deve ser estimulada. Estudo (11) demonstrou que o desconhecimento sobre o HPV e sua vacinação leva à relutância dos pais em vacinar seus filhos, enquanto a percepção de risco pela infecção do HPV associou-se positivamente a adesão a vacinação.…”
Section: Discussionunclassified
“…Applying country-specific data in relation to 30 pre-defined available attributes [13][14][15][16][17][18][19][20][21][22][23][24][25], we found that only 10 attributes gave different impact on prioritizing new vaccines since they had significant difference values among four new vaccines. These attributes are: (i) premature deaths averted per year, (ii) incident cases prevented per year, (iii) quality-adjusted life years (QALYs) gained or disabilityadjusted life years (DALYs) averted, (iv) net direct costs (savings) of vaccine use per year, (v) workforce productivity gained per year, (vi) cost-effectiveness, (vii) benefits for infants and children, (viii) benefits for women, (ix) availability of existing or adaptable manufacture techniques, and (x) interest from NGOs and philanthropic organizations.…”
Section: Resultsmentioning
confidence: 99%